Pain management in the elderly - Boland, Michael; Burns, Pru.; Seidel, Paul.; Video Education Australia (Bendigo, Vic. : Video Education Australia, 2010)
Pain is something we all experience and is something that many people fear, especially as they grow older. Long term experiences of pain may well become increasingly common as we head towards an ageing society beset with multiple chronic diseases. It is therefore imperative that medical professionals understand the implications of pain and incorporate appropriate actions to assess and deal with pain into their patient care. This program considers all of these issues and looks broadly at pain management in the elderly. Three pain management experts share their insights with us, examining what pain is, assessment methods and common treatments available.
Disc characteristics: DVD Region Universal.
Writer/director/producer, Michael Boland ; senior producer, Pru Burns.
Narrator, Paul Seidel.
Keywords: Pain -- treatment; Older people -- Care